IMPLEMENTASI SISTEM INFORMASI PENDATAAN PENDUDUK PADA PERUMAHAN BATOLA RESIDENCE BERBASIS WEB - Abdullah Ardi (TEKNIMEDIA: Teknologi Informasi dan Multimedia, 2023)
Batola Residence housing is one of the residential institutions provided by the government for the lower middle class people with adequate facilities and infrastructure for housing residents. Management and storage of population data is still done in a manual way such as archived in a copy of the book. This resulted in less than optimal service to citizens because it takes a long time to get accurate information. The system used to manage population data can assist Block Chairs and Officers in matters of service to residents such as making reports or correspondence related to the population of Batola Residence Housing. This system was developed using the SDLC Methodology (System Development Life Cycle) waterfall model with the stages of communication, planning, modeling and construction. At the system design stage using ERD (Entity Relationship Diagram) and DFD (Data Flow Diagrams), namely Context Diagram, DFD Level 1 and DFD Level 2. The web development framework uses the Codeigneter Framework, which contains and arranges the programming languages PHP, HTML, and Javascript , and the MySQL query language. In the last stage for system testing using the Black Box Testing technique to get the results of all features running smoothly and the results of testing this system are in accordance with functional requirements.